THE ABSENCE OF MOTHER: THE RELATIONSHIP OF FATHER DAUGHTER IN GOTHIC FICTIONS - Ayu, Hujuala Rika (Paramasastra, 2017)
This paper discusses the bonding of father and daughter in Angela Carter?s ?The Courtship of Mr. Lyon? and Intan Paramaditha?s ?Pintu Merah? (transl. ?The Red Door?). Carter and Paramaditha employ distinguished narrative structures to highlight the interaction among the characters. They utilizes third-person narrator and reproduces fairy tales. The absence of mother becomes an interesting pivot in both stories. In that situation, father is inevitably the daughter?s closest figure. In both stories, fathers are at the same time demanding and lame. While, daughters are those dependent, submissive yet tactical figures in facing their fathers as the sole counterparts in the story. Using the perspectives of Juliett Michelle and Nancy Chodorow on psychoanalysis feminism, this paper unveils the roles of father in daughter?s adolescent development. This study reveals that despite the dependencies of the daughters toward the familial relationship, they use their submissiveness as the weapons to break the patriarchal values represented by the fathers.